MEDIA BOOKLET INFORMASI PROMOSI KEPARIWISATAAN DINAS PARIWISATA DAN EKONOMI KREATIF PROVINSI SUMATERA BARAT - DEDI KURNIA, Hendra Afriwan, S.Sn., M.Sn., Ir. Drs. Heldi, M.Si., Ph.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The tourism of development in West Sumatra has began to show some seriousness into improvement about tourism programs. However, there’s still need to gain information and communication of tourism which will be need to improve akuratly, easily, and quickly obtained overview of the existing tourism in West Sumatra. So farness it doesn’t show how optimal the information and promotion performances do it by Departement of Tourism and Creative Economy of West Sumatra, true print media so than will be need a booklet design with some source’s of information.The purpose of design is to produce a booklets as communication and information as well as promotion for the need of tourists who visit West Sumatra.First of all a design is convicted with main data: documentation, interview and observation, while additional data is began with book’s, education journal, and internet. Approaches of using data analysis 5W + 1H ( what, where, where, when, who, why, how) with maniest questions and answers as it’s troubleshooting key. The booklet is selected for main media as well is supported: Backdrop, Calendar, Mug, papperbag, pin, Poster, sticker, and x-banner.Keywords: Tourism, Promotion, Booklet